Survei Tingkat Kesegaran Jasmani Siswa Kelas VIII SMPN 1 Pademawu Pamekasan - Apriyadi, Rian Bahtiar; Handayani, Heni Yuli; Purwoto, Septyaningrum Putri (MAN Insan Cendekia Jambi, 2025)
This study concludes that the physical fitness level of grade VIII students at SMPN 1 Pademawu Pamekasan is overall in the